An Analysis of Improved Interest and Learning Outcomes in Mathematics at Junior High School RME Teaching Model - Moch. Fauzi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2024)
The problem behind this research is the lack of student interest in learning and the results of grades in mathematics in class VII. Class VII students' interests and grades in mathematics subjects can be seen from students' understanding of mathematics subjects and internal and external factors. The objectives to be achieved in the research are (1) to determine students' interest in learning using the Realistic Mathematic Education learning method, and (2) to determine student learning outcomes when using the realistic mathematical education method. The type of research used in this research is qualitative research. The instruments used in this research were initial and final student interest questionnaires, interview guide sheets, and student test questions. Based on the research results, it can be seen that: (1) the lack of interest in learning and the results of grade VII students in mathematics subjects, namely that students are lazy and sleepy when learning mathematics and consider mathematics to be a boring lesson. (2) the cause of students' lack of interest is seen from the results of questionnaires and interviews, namely that students lack interest in mathematics due to internal and external factors. Based on the research results, it can be concluded that students' lack of interest in mathematics lessons can be seen from internal factors consisting of attention and willingness, while external factors consist of changes in the teacher's teaching methods